Blockchain‐based privacy‐preserving valet parking for self‐driving vehicles. Issue 4 (10th March 2021) - Fang, Yunyi; Zhao, Yanqi; Yu, Yong; Zhu, Hui; Du, Xiaojiang; Guizani, Mohsen
Abstract: The valet parking provides convenience for users and thus is becoming increasingly popular nowadays. However, this valet parking service incurs the risks of location information leakage and vehicle theft. To address these issues, in this paper, we propose a blockchain‐based privacy‐preserving valet parking protocol (B‐park) for self‐driving vehicles. The protocol guarantees the privacy of users while providing transparency and auditability of the valet parking service. We define the system model of privacy‐preserving valet parking for self‐driving vehicles in blockchain setting and formalize its security properties including anonymity, conversion blindness, nonframeability, and traceability. We provide a concrete construction of B‐park as well based on a new variant of Pointcheval‐Sanders group signature. Then, we demonstrate that our protocol is secure in the random oracle model. Finally, we evaluate the performance of B‐park to demonstrate its effectiveness and practicability. Abstract : We propose a blockchain‐based privacy‐preserving valet parking protocol called B‐park for self‐driving vehicles. The protocol guarantees the privacy of users while providing transparency and auditability of the service of valet parking.